(untitled) (ELEKTRIKA- Journal of Electrical Engineering, 2023)
This paper presents the substrate comparison on the multiband reflector performance at X-band frequency for an Intelligent Reflecting Surface (IRS). Functioning as a multiband reflector, the proposed reflector is using a circular multi-ring resonator on several substrates such as RO5880, F4BMX220, RO4003C, and FR4, with slightly different substrate thicknesses based on the available market, that can be operated at X-band frequency. The simulated results have shown in the graph of S-parameters and reflection phase among the substrates. In addition, the bandwidth of the proposed reflector is calculated based on the simulation results. Also, the incident wave angle effect against the proposed reflector is shifted along the horizontal axis. For the overall simulation results, the reflector that uses a RO5880 substrate has slightly better results and a wider bandwidth than the F4BMX220 substrate.